STRATEGI ADAPTIF DAN INKLUSIF DALAM MEMBANGUN SISTEM PENDIDIKAN NASIONAL YANG BERKELANJUTAN - Mas Fierna Janvierna Lusie Putri (Educatus, 2023)
Indonesia's national education system is currently undergoing a complex transition amid the demands of globalization, technological advancements, and public expectations for a more relevant and inclusive system. This study aims to analyze adaptive and inclusive strategies in building a sustainable national education system. The method used is a qualitative literature study with a thematic analysis approach to policy documents, scientific articles, and relevant institutional reports. The findings indicate that although policies such as *Merdeka Belajar* have been initiated to improve the quality and equity of education, their implementation still faces several challenges, including disparities in teacher quality, limited infrastructure, and digital gaps between regions. Furthermore, 21st-century competency-based education has not yet been fully integrated into the existing learning system. This research emphasizes the importance of a holistic, flexible, and data-driven approach to educational reform in order to address the multidimensional challenges currently faced. The implications of these findings highlight the need to strengthen collaboration between the government, society, and other stakeholders in designing educational strategies that are responsive to changing dynamics and oriented toward long-term equity and sustainability.